KARAKTERISASI TANAMAN JERUK (Citrus sp.) DI KECAMATAN NIBUNG HANGUS KABUPATEN BATU BARA SUMATERA UTARA - Miza Nina Adlini; Hafizah Khairina Umaroh (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
Citrus is one of the horticultural plants found in Indonesia and is in great demand. The diversity of oranges is very high as indicated by the number of Citrus members. North Sumatra is one of the province with high citrus productivity. Therefore, this study aims to identify the diversity of citrus plants based on their morphological characters in  Nibung Hangus area, Batu Bara, North Sumatra. Data were collected by exploration method. Morphological identification is carried out to assess the morphological diversity of samples taken at the study site, including visual observations of the size, shape and color of plant organ parts. The organs observed included the stems, leaves and fruit of citrus plants. Morphological characterization using the guidelines in IPGRI and the book of Tjitrosoepomo (2002). The data analysis was carried out in a descriptive qualitative. The results showed that there were 5 types of citrus plants found in Nibung Hangus, namely Pamelo Plant (Citrus maxima), Lime Plant (Citrus aurantifolia), Tangerine Plant (Citrus reticulata blanco), Kaffir Lime Plant (Citrus hystrix), and Sunkist Citrus Crop (Citrus sinensis).